FRESH-WATER GREEN ALGAE (CHLOROPHYTA) AS A NATURAL PIGMENT FOR MOJOSARI DUCKS - Indarsih, B.; Asnawi, A.; Purnamasari, D.K. (Diponegoro University, 2015)
An experiment in a completely randomize design was undertaken to study the use of fresh-watergreen algae as a yolk coloring agent in Mojosari ducks during a laying period on productiveperformance and egg quality from 36 to 44 wk of age. A total of 80 thirty-six wk–old laying ducks weredivided into four dietary treatments and each of four replicates with 5 birds. Diets were formulated witha commercial concentrate, rice bran and yellow corn (2:4:4) according to a commercial standard diet asa control, and three other dietary treatments with 2, 4 or 8% of green algae were included. Fresh watergreen algae had a significant effect on the feed uptake, egg production, and feed conversion ratio (FCR)(p<0.05). Egg production and FCR improved at added 2 and 4% green algae. No differences wereobserved in egg yolk index, albumen index, Haugh Unit, and egg shell thickness (P>0.05) except eggyolk color. The yolk color increased within 7 days after feeding with the test diets. The present studyindicated that fresh-water green algae could be used as a natural coloring agent in laying ducks and at8% of green algae showed the highest score of (Roche Yellow Color-15).